Housing and Urbanization in Africa: Unleashing a Formal Market Process - Paul Collier (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
In many African countries a market for private provision of formal sector mass housing is largely absent. This is not inevitable, but is the consequence of policy failure surrounding five key issues. The affordability of housing, with costs often inflated by inappropriate building regulations and inefficient construction sectors; lack of clarity in land titling and legal enforcement; lack of innovation in supply of housing finance; failure to supply supporting infrastructure and to capture development gains to finance this; and failure to plan cities in a manner conducive to employment creation. Since responsibility for these policies is divided between different parts of government, a coordinated push is needed to secure reform and activate this market.
Keywords: O18; P52; D23; 330